Contributions of asthma, rhinitis and IgE to exhaled nitric oxide in adolescents. Issue 2 (19th April 2021) - Flashner, Bess M.; Rifas-Shiman, Sheryl L.; Oken, Emily; Camargo, Carlos A.; Platts-Mills, Thomas A.E.; Workman, Lisa; Litonjua, Augusto A.; Gold, Diane R.; Rice, Mary B.
Exhaled nitric oxide fraction ( F eNO ) is an indicator of allergic airway inflammation. However, it is unknown how asthma, allergic rhinitis (AR) and allergic sensitisation relate to F eNO, particularly among adolescents and in overlapping conditions. We sought to determine the associations between asthma, AR, and aeroallergen immunoglobulin (Ig)E and F eNO in adolescents. We measured F eNO among 929 adolescents (aged 11–16 years) in Project Viva, an unselected prebirth cohort in Massachusetts, USA. We defined asthma as ever asthma physician diagnosis plus wheezing in the past year or taking asthma medications in the past month, AR as a physician diagnosis of hay fever or AR, and aeroallergen IgE as any IgE >0.35 IU·mL −1 among 592 participants who provided blood samples. We examined associations of asthma, AR and IgE with percent difference in F eNO in linear regression models adjusted for sex, race/ethnicity, age and height, maternal education and smoking during pregnancy, and household/neighbourhood demographics. Asthma (14%) was associated with 97% higher F eNO (95% CI 70–128%), AR (21%) with 45% higher F eNO (95% CI 28–65%), and aeroallergen IgE (58%) with 102% higher F eNO (95% CI 80–126%) compared to those without each condition, respectively. In the absence of asthma or AR, aeroallergen IgE was associated with 75% higher F eNO (95% CI 52–101), while asthma and AR were not associated with F eNO in the absence of IgE. The link between asthma and AR with F eNO is limited to those with IgE-mediated phenotypes. F eNO may be elevated in those with allergic sensitisation alone, even in the absence of asthma or AR. While asthma, allergic rhinitis (AR) and allergic sensitisation are associated with higher F ENO, asthma and AR in the absence of aeroallergen IgE are not associated with F ENO . When elevated in asthma or AR, F ENO suggests allergic sensitisation. https://bit.ly/3bGgr0r